2021
DOI: 10.3390/antiox10081279
|View full text |Cite
|
Sign up to set email alerts
|

Wide Spectrum of Active Compounds in Sea Buckthorn (Hippophae rhamnoides) for Disease Prevention and Food Production

Abstract: Growing demand for value-added products and functional foods is encouraging manufacturers to consider new additives that can enrich their products and help combat lifestyle diseases. The healthy properties of sea buckthorn have been recognized for centuries. This plant has a high content of bioactive compounds, including antioxidants, phytosterols, essential fatty acids, and amino acids, as well as vitamins C, K, and E. It also has a low content of sugar and a wide spectrum of volatiles, which contribute to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 95 publications
0
33
0
Order By: Relevance
“…In China, Russia, Mongolia, Turkey and many other places, sea buckthorn is used as a folk medicine to treat stomach ulcers, cough, skin diseases, jaundice, asthma, high blood pressure, rheumatism and genital inflammation [2,3]. In addition to being used as a pharmaceutical, sea buckthorn can be used in food and cosmetics [4]. Modern research has shown that sea buckthorn berries are rich in a variety of bioactive constituents and nutrients: hydrophilic compounds (phenolic acids, flavonoids, ascorbic acid), lipophilic antioxidants (vitamins, Molecules 2021, 26, 7189 2 of 16 carotenoids, tocopherols), protein and amino acids, lipid compounds and fatty acids, sugars and polysaccharides, mineral elements, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, Russia, Mongolia, Turkey and many other places, sea buckthorn is used as a folk medicine to treat stomach ulcers, cough, skin diseases, jaundice, asthma, high blood pressure, rheumatism and genital inflammation [2,3]. In addition to being used as a pharmaceutical, sea buckthorn can be used in food and cosmetics [4]. Modern research has shown that sea buckthorn berries are rich in a variety of bioactive constituents and nutrients: hydrophilic compounds (phenolic acids, flavonoids, ascorbic acid), lipophilic antioxidants (vitamins, Molecules 2021, 26, 7189 2 of 16 carotenoids, tocopherols), protein and amino acids, lipid compounds and fatty acids, sugars and polysaccharides, mineral elements, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 , 6 ]. The berry has been shown to possess antioxidant, antibacterial, cytoprotective, antitumor, anti-inflammatory, immunomodulatory, antifatigue and anticholinergic activities [ 3 , 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The importance of sea buckthorn is often attributed to its high levels of natural antioxidants, of which polyphenols and flavonoids are important components [ 1 , 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sea buckthorn (Hippophaë rhamnoides L.; Elaegnaceae) is a shrubby plant naturally distributed over Asia and Europe [1,2] producing tasty orange fruits that have been widely used in traditional medicine since ancient times [3]. Various parts of the plant, and especially its fruits, are sources of many bioactive compounds with antioxidant, antiinflammatory, analgesic, anti-cancer, antibacterial and antiviral activities [4][5][6][7]. Berries of sea buckthorn (SB) are a high nutritional value fruit with a plethora of bioactive ingredients and the exceptional value of them is attributed to the presence of both lipophilic antioxidants (mainly carotenoids and tocopherols) and hydrophilic antioxidants (flavonoids, tannins, phenolic acids, ascorbic acid) in significant high quantities [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Various parts of the plant, and especially its fruits, are sources of many bioactive compounds with antioxidant, antiinflammatory, analgesic, anti-cancer, antibacterial and antiviral activities [4][5][6][7]. Berries of sea buckthorn (SB) are a high nutritional value fruit with a plethora of bioactive ingredients and the exceptional value of them is attributed to the presence of both lipophilic antioxidants (mainly carotenoids and tocopherols) and hydrophilic antioxidants (flavonoids, tannins, phenolic acids, ascorbic acid) in significant high quantities [7][8][9][10]. SB oil from whole berries has a unique content (palmitoleic acid, n-7 and γ-linolenic acid, n-6) and balanced composition of fatty acids with beneficial effects for human health [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation